Studi Korelasi Tingkat Stres Kerja pada Pegawai di Kantor Kesehatan Pelabuhan Kelas 1 - emmi Bujawati; Lilis Widyastuti; Ranti Ekasari; Tri Addya Karini; Nurul A Fajriani; Rosmilasari Rosmilasari; Windasari Putri; Andi A. Muslim (Politeknik Baubau, 2023)
Stress is a negative reaction experienced by workers due to excessive work at work. This study aims to determine the correlation of gender, level of education and years of service with the level of work stress on employees at the Makassar Class 1 Port Health office. The population and sample of this study were all employees at the Makassar Class 1 Port Health Office totaling 30 people. The stress measuring tool used is the Stress Diagnosis Survey (SDS) observation sheet. The results showed that there was a correlation between gender (P= 0.00 and R= 0.8) working period (P=0.00, R=0.7) and work stress and there was no correlation between education level (P=0.38 and R= 0.2) and stress. work. Therefore, it is necessary to have regulations related to work rotation or adjustment of workload to the level of ability possessed by employees and to create a conducive work environment